Guía Didáctica de MegaStat para el Aprendizaje de Estadística Inferencial - Calo Macas, Jefferson Eduardo (2024)
The teaching and learning of Inferential Statistics satisfy the demand of offering teachers and students innovative resources that facilitate the understanding of applying inferences of populations from samples. That is why the present investigation aimed to elaborate a Didactic Guide of MegaStat for the Learning of Inferential Statistics for Students of the Career of Pedagogy of Experimental Sciences: Mathematics and Physics of the National University of Chimborazo. The methodology used had a quantitative and transversal approach since the data were collected in a certain period of time, as a data collection technique, a structured survey with fifteen questions was used, which was directed to the students of the eighth semester of the Pedagogy of Experimental Sciences: Mathematics and Physics of the National University of Chimborazo. As a result, it became evident that most of the students had several problems in learning the subject, among which it was difficult for them to differentiate between parametric and non-parametric tests, and it was also difficult for them to interpret the results using the p-value method and to apply the statistical tests in the software. As a result of this research, a didactic guide on using MegaStat for learning inferential statistics was developed, which becomes a valuable resource that contributes to the teaching-learning process of the subject.